New and significant avifaunal records from Batam and Bintan Islands, Riau Archipelago - Andrew Crossland; S. A. Sinambela (KUKILA, 2014)
Observations made during 2000-2003 and 2012, mainly in estuarine and other coastal habitats, increase the list of bird species known from Batam and Bintan islands by 15 (to 137) and two species (to 181) respectively. These records include five species new for the Riau Archipelago (Red-tailed Tropicbird Phaeton rubricauda, Cattle Egret Bubulcus ibis, Wood Sandpiper Tringa glareola, Curlew Sandpiper Calidris ferruginea and House Crow Corvus splendens). We also present additional records of species previously noted as uncommon or of restricted distribution in the region. Differences between the Riau Archipelago and nearby Singapore in the total number of known bird species (229 and 375 species, respectively) may be partly due to their relative isolation from mainland Southeast Asia, but the much greater survey effort on Singapore over many years must also be a significant factor. Additional, hitherto unpublished, observations by birdwatchers are sought to assess the relative importance of these explanations.